The Performance Of Legislative Secretariat Services: Perspective Of The New Public Service - Rasyid, Abdul; Albarbassy, Ma’mun Murod; Satispi, Evi; Samudra, Azhari Aziz (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2022)
The Regional People's Representative Council (DPRD) is part of the local government in a decentralized system. The responsibilities of the DPRD include three main things: development supervision, budgeting, and legislation. All three functions are carried out within the framework of community representation. The implementation of these three functions is supported by the DPRD secretariat device, whose duties/functions and authorities have been regulated in Government Regulation Number 18/2016 concerning Regional Devices. The duties and responsibility of the DPRD secretariat are to provide services to members of the DPRD. This study aims to analyze the quality of services from a new public service (NPS) perspective. For this reason, the study develops ten new public service indicators. The sampling technique was carried out using purposive/judgment sampling. Purposive/judgment sampling is a technique based on the researcher's consideration of several suitable characteristics relating to the sample members needed to answer the research objectives. All indicators are tested using Importance Performance Analysis, one of the statistical techniques to test the degree of importance of an aspect. To answer the formulation of the problem, this study provided a questionnaire (Likert scale) to fifty DPRD members. As a result, out of the ten NPS indicators, the courtesy indicator is included as the top priority that the DPRD secretariat of the Tangerang Selatan Municipality must complete. In addition, tangible indicators, competence, communication, and customer understanding are included in the low priority. Further elaboration of these results is presented in this paper